Custodian farmers of agricultural biodiversity: selected profiles from South and South East Asia: proceedings of the workshop on custodian farmers of agricultural biodiversity, 11-12 February 2013, New Delhi, India - Sthapit, B.R.; Lamers, H.; Rao, R. (Bioversity International, 2013)
The publications presents the proceedings of the Workshop on Custodian Farmers of Agricultural Biodiversity, 11-12 February 2013, New Delhi, India. About 20 farmers from five countries (India, Indonesia, Malaysia, Nepal and Thailand) participated in the workshop and shared their experience and motivations. The workshop also debated on the challenges faced by such farmers and discussed the ways to strengthen and/or support them so that they continue to use, conserve and promote agricultural biodiversity. The meeting also produced recommendations to policy makers to support on-farm conservation efforts.